Arte, terapia y transformación social en la intersección entre postestructualismo y teoría crítica - Suess, Astrid (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
Identifying contemporary art, tendencies in psychotherapy, creativity theories, art education and group dynamics as epistemological sources for the emergence of Art Therapy in the mid-20th century, this article asks for the current discursive space art therapy practice is inserted. Theoretical assumptions from two philosophical approaches, post-structuralism and contemporary critical theories, were reviewed to find out its potential relevance for art therapy in the current socio-political context. In addition of reflecting on the potentialities and challenges these theories raise for psychotherapeutic practice, the review highlights certain art therapy experiences which were carried out from both conceptual frameworks, as a result of the interest in discovering new approaches for patients in the 21st century.